2005
DOI: 10.1002/cncr.20902
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bladder carcinoma by combined testing of urine for hyaluronidase and cytokeratin 20 RNAs

Abstract: BACKGROUNDA new, sensitive, noninvasive method for the detection of urothelial carcinomas of the urinary bladder would open new possibilities in both the diagnosis and followup of patients.METHODSThis study included 228 patients diagnosed with bladder carcinoma, 68 patients with benign bladder lesions, and 44 healthy persons served as the control group. All were subjected to: serologic schistosomiasis antibody assay in serum, urine cytology, estimation of urine hyaluronic acid (HA) by enzyme‐linked immunosorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Conventional RT-PCR for detection of CK20 mRNA Detection of CK20 by RT-PCR was done in urine and optimized as previously described [14]: 2 lg of total RNA was subjected to first-strand cDNA synthesis using Maloney murine leukemia virus (MMV) reverse transcriptase and oligo primer pd (T) [12][13][14][15][16][17][18] for 1 h at 42°C. RT-PCR was performed using the Ready-to-Go TM RT-PCR Beads (0.2 ml tubes) (Amersham Pharmacia Biotech, Piscataway NJ).…”
Section: Rna Extractionmentioning
confidence: 99%
“…Conventional RT-PCR for detection of CK20 mRNA Detection of CK20 by RT-PCR was done in urine and optimized as previously described [14]: 2 lg of total RNA was subjected to first-strand cDNA synthesis using Maloney murine leukemia virus (MMV) reverse transcriptase and oligo primer pd (T) [12][13][14][15][16][17][18] for 1 h at 42°C. RT-PCR was performed using the Ready-to-Go TM RT-PCR Beads (0.2 ml tubes) (Amersham Pharmacia Biotech, Piscataway NJ).…”
Section: Rna Extractionmentioning
confidence: 99%
“…The increased hyaluronidase levels in bladder cancer patients are due to increased HYAL1 expression in bladder tumor cells both at the transcriptional and protein levels (16)(17)(18). HYAL1 expression is a potential prognostic indicator for prostate cancer progression and a possible marker for detecting head and neck squamous cell carcinoma (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR and cDNA cloning, protein purification, immunoblotting, pH activity profile and immunohistochemistry have revealed that HYAL-1 is the major tumor-derived HAase expressed in prostate and bladder carcinoma cells with invasive/metastatic potential (Lokeshwar et al, 1999;Csoka et al, 2001;Lokeshwar et al, 2001;Eissa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%